Re-visioning Design Education: A Third Culture Epistemology - Cline, Thomas J (ARCC Conference Repository, 2014)
Traditionally, education has been theorized as existing within a binary system”education inthe sciences and education in the humanities. If education in design can be viewed as a third culture within this realm then it will have teachers that teach design, students that learn design, and mechanisms in place to insure that the teaching and learning of design occur. Resultantly, one must ask: What does it mean to know as a designer? This question is one of epistemic significance, and, as such, begins to create the basisof a framework for design knowledge and design education. What, in a newly categorized third culture, can establish such an epistemic foundation; are the epistemic models available in the sciences and humanities appropriate for design education? How can education in design both situate itself in relation to the sciences and the humanities while providing for an epistemic foundation that allows for design knowing, design teaching, and design learning? It is the intention of this paper to explore a qualitative and philosophical inquiry that positions design education; a position that interrogates a two-culture epistemology of education and begins to allow for a third culture whose knowledge is founded upon its own epistemic authority. This positionality will be addressed by exploring design education in relation to traditional education, outlining and engaging the problematic assumptions of the historical emergence of design education, and then proposing a return to the virtues of durability, utility, and beauty as proposed by Vitruvius in his foundational text De Architectura (1st CenturyBC). This return to Vitruvian virtue re-theorizes a design epistemology”and; therefore, a design education”that is once again grounded in the material, the contextual, and the experiential. By way of this Vitruvian re-visioning”a re-visioning that positions design education firmly within a pragmatic and material world”the content of that education is expunged from the store of tradition and made available to all learners through the uniqueness and complexity of individually lived experience.